ChemInform Abstract: Gold(I)‐Catalyzed 1, 4‐ and/or 1, 5‐Heteroaryl Migration Reactions Through Regiocontrolled Cyclizations. Issue 23 (June 2015) - Wang, Chengyu; Xie, Xin; Liu, Jun; Liu, Yuanhong; Li, Yuxue
Abstract This reaction provides a concise access to stereodefined trisubstituted alkenes by endo cyclization with concomitant 1, 5‐migration of the furanyl group in the presence of unactivated molecular sieves.